High-resolution sequential thermal fringe projection technique for fast and accurate 3D shape measurement of transparent objects - Landmann, Martin; Speck, Henri; Dietrich, Patrick; Heist, Stefan; Kuehmstedt, Peter; Tuennermann, Andreas; Notni, Gunther (Applied Optics, 2021)
Three-dimensional (3D) shape measurement systems based on diffuse reflection of projected structured light do not deliver reliable data when measuring glossy, transparent, absorbent, or translucent objects. In recent years, we have developed a method based on stereo recording with infrared cameras and projection of areal aperiodic sinusoidal thermal patterns to detect such objects. However, the measurements took longer than 10 s, up to minutes; moreover, the measurement accuracy was improvable. Now, we have succeeded in both drastically reducing measurement time and significantly increasing measurement quality. This finally provides a technique for reliably measuring transparent objects, e.g., in series production. We demonstrate measurement examples achieved within 1 s and with 3D standard deviations less than 10 µm.
CRIS-Team Scopus Importer:2023-04-20